Symposium 3: Where is the learning in networked knowledge construction? - Zenios, Maria; Goodyear, Peter (Proceedings of the International Conference on Networked Learning, 2008)
From the days of Plato until today’s information society, knowledge has been at the core of human activity critically influencing aspects of social, cultural and economic prosperity across communities. The emergence of networked communication technologies has dropped traditional boundaries in H.E. allowing bringing together geographically dispersed learners and giving them opportunities to redefine their shared understanding of a given discipline as well as a shared sense of their complex roles as developing professionals. Increasing attention is being paid to the ways in which values, beliefs, experiences and knowledge are being shared and negotiated among groups of learners in formal educational settings. Networked learning in particular, provides a range of collaborative learning arrangements that include a broad variety of networked computer technologies and has become a useful context for knowledge construction in H.E. What is interesting in exploring knowledge construction learning communities is placed on discussions pointing to the distinction between the creation of collaborative knowledge and possibilities for learning emerging from such initiatives. There is also a need for research on the ways in which the experiences gained from collaboration are used to deal with emerging learning situations, e.g. those met while preparing assignments and project reports as part of a formal course of study. The process of collaborative knowledge construction often involves cycles of developmental activity in which participants engage including decisions about what is worth to be added to the knowledge of a learning community. As a useful conceptual tool for researching the process of knowledge construction in networked learning, we propose the notions of epistemic activity and epistemic fluency. The epistemic ideas, we argue, work as a useful framework to give meaning and to refine collaborative discussion prone to the generation of new knowledge. This work-in-progress paper develops the conceptual background for researching knowledge construction in networked learning and examines learners’ participation in knowledge advancement activities both collaboratively and individually through the lens of qualitative methodology. Learners’ participation in knowledge construction activities is investigated using an analytical framework originating from the data and ideas guided by the theoretical framework of the study. Data have been collected from a postgraduate course in Advanced Learning Technology including online discussions, student assignments and interviews. The paper concludes that the ideas expressed within online messages exchanged between course participants as well as research projects and reviews undertaken as part of their assessment are representations of abstract knowledge. Epistemic activities have a decisive role in knowledge creation and improvement as they add value to such representations. Participation in epistemic activities inherent in a professional culture or discipline (i.e. through answering important questions, solving out problems and adding to its knowledge base) allows gradually becoming an active valued practitioner of this culture and generally develops one’s epistemic fluency. Finally, the findings point to the importance of the contextual aspect in the process of knowledge construction and epistemic fluency acquisition pointing to the fact that knowledge can be advanced through interaction of the individual with the environment including peer learners, tutors and available resources. The ability to create and refine knowledge while maintaining a set of relations between other learners, resources and communities has implications for learning. Connectivity is crucial to that extend. In that respect, networked learning needs to be redefined to emphasise the dynamic attributes inherent in the connections enabled between participants and resources which are conducive to the emergence of shared and new knowledge. The implications for transformational learning found in such initiatives remain to be further explored.